Air quality issues in the environmental impact statements of housing projects - Al-Madhoun, W.A.; Ramli, N.A.; Isa, M.H.; Adlan, M.N.; Razman, M.R. (2004)
Air Quality Issue has important concern because of the negative effects of air pollution on human beings and environment as well. This paper describes the result of a review of Air Quality Issue consideration in 25 Environmental Impact Statements (EIS) prepared for housing projects that has obtained the approval from the Department of Environment - Malaysia. The results show that 84% of the studied reports need detailed assessment, in 52% of the reports the monitoring methods was studied in good way, impact identification and prediction in 56% of the reports was addressed briefly and in 80% of the reports, the mitigation measures were explained briefly. It can be concluded that more concern should be given to the monitoring of the pollutants i.e. CO, CO2, NO2, and SO2 not only TSP. The DOE should determine standard mitigation measures for the housing projects and the DOE should impose conditions on the proponent so that he will be committed to implementation of the mitigation measures.